Audit on parental awareness of minimising added sugar intake during complementary feeding - Florence Chang; Rachael Hocking; Emma Hingston; David Tuthill (Clinical Medicine)
Objectives: The NHS recommends that children aged 4 years and below avoid any food and beverages with added sugar.1 We audited against this with a survey. This study aimed to evaluate parental awareness on added sugar intake during complementary feeding. Design: A survey was created with 21 questions covering the child’s demographics, advice parents were given, their source of information, importance of minimising sugar to parents, use of store-bought baby food, identifying food with added sugar, and dental questions. A pilot survey was done with five parents to achieve clarity. Results: 128 parents with children under 5 years old were approached, of these 12 declined, 15 did not complete the survey and one could not speak fluent English. Of the remaining 100 children: • 50 were boys and 50 were girls. • 38% of the children were the first child. • The age groups were as follows: under 1 year old (21%), 1-year old (20%), 2-years old (19%), 3-years old (22%) and 4-years old (18%). • 33% were breast fed, 33% were formula fed, 32% combination fed and 2% fed using selected other methods. • Most parents (80%) were given advice on when to start complementary feeding. • 63% of the parents followed the recommended age to start complementary feeding, which is 6-months old; • 31% did it earlier than the recommended age, whereas 6% did it later; • 77% of the parents followed the advice given to them on the time to start complementary feeding • Only 25% of parents said they had all the information needed about complementary feeding. • The main sources of information about complementary feeding were: 4% doctor; 55% health visitor; 22% websites and online resources; 2% social media; 4% friends and relatives; 13% other • Most parents (81%) considered minimising sugar intake when introducing solids. • 43% of parents said reducing sugar intake was a very important factor to them; • 90% of parents said they were aware of ‘added sugar’ and that they should avoid it during complementary feeding; • Most parents described added sugar as ‘extra artificial sugar not originally present in food’; • Some parents (14%) used store-bought baby food on a daily basis, while 33% used it few times a week.Most parents failed to identify the products with added sugar (Fig 1).70% of parents were aware that they should start brushing their child’s teeth as soon as the first tooth had erupted. For the 60% of children who had had their dental check-up, 78% of them had it when they were 1 year old and below. Conclusion: • Parents with multiple children have better complementary feeding knowledge; • Most parents claimed to know what added sugar is and to avoid it when complementary feeding; however, most were unable to recognise products with added sugar; • Parents had a wide variety of sources of information about complementary feeding; • Most parents had a general understanding of added sugar.